Exploring Behavioral and Motivational Determinants of Employee Performance in the Finance Industry - Sharla Martiza; Maidiana Astuti Handayani (The Indonesian Institute of Science and Technology Research, 2026)
Employee performance is a critical factor influencing organizational effectiveness and competitiveness in the financial services industry. This study examines the effects of work discipline, employee loyalty, and work motivation on employee performance at PT Mandala Finance Tbk., Palembang Branch, Indonesia. A quantitative explanatory research design was employed using a survey method. The study population consisted of 153 permanent employees, from whom 111 respondents were selected through proportionate stratified random sampling. Data were collected using a structured questionnaire and analyzed using multiple linear regression. Instrument testing confirmed satisfactory validity and reliability, with Cronbach’s alpha coefficients ranging from 0.752 to 0.851. The results indicate that work discipline, employee loyalty, and work motivation simultaneously have a significant effect on employee performance (F = 37.170, p < 0.001). Individually, work discipline (β = 0.271, p = 0.002), employee loyalty (β = 0.277, p = 0.006), and work motivation (β = 0.459, p < 0.001) positively and significantly influence employee performance. The coefficient of determination (R² = 0.510) shows that the three variables explain 51.0% of the variance in employee performance. Among the predictors, work motivation emerged as the strongest determinant. The findings highlight the importance of integrating disciplinary practices, loyalty-building initiatives, and motivational strategies to enhance workforce performance in the finance industry.